Conceptualization and validation of the TILT questionnaire: relationship with IGD and life satisfaction - Bonilla, Iván; Chamarro, Andrés; Birch, Phil; Sharpe, Benjamin T.; Martín-Castellanos, Adrián; Muriarte, Diego; Ventura, Carles (Frontiers in Psychology, 2024)
Currently, the study of esports is growing within the field of psychology. Among the different variables attracting interestincluding stress or psychological factors associated with performancean emerging concept known as tilt is gaining prominence in the literature.However, this construct has yet to be operationalized or defined. Thus, the present study aims to address this gap by defining and conceptualizing TILT while devising and validating a questionnaire to measure the construct in esports players.The initial phase of the study comprised 27 interviews conducted with professional players (n = 6), semi-professionals (n = 8), amateurs (n = 8), and coaches (n = 5) to characterize the concept of tilt.Following these interviews, a definition of tilt was formulated, and a panel of five experts in sports psychology and esports proposed a comprehensive set of 53 items. A total of 488 participants (278 males, 210 females), aged 18-50 (mean age = 26.9 years, SD = 7.57), completed the survey, including the 53 tilt items, a questionnaire measuring toxic behavior, and the Internet Gaming Disorder Scale-Short Form (IGDS9-SF).The tilt construct is primarily characterized as a state of frustration escalating into anger, resulting in diminished performance, attention, and recurring negative thoughts about errors.Its onset typically coincides with stressful situations, persisting for approximately 30 minutes.Through an Exploratory Factor Analysis (EFA), 18 items were retained and categorized into two factors: Causes (7 Items) and Consequences (11 Items) of tilt. The entire questionnaire yielded a Cronbach's α of 0.922, with the first and second factors showing values of 0.854 and 0.890, respectively. Confirmatory factor analysis (CFA) revealed an acceptable fit for the 2factor solution. Correlations with related constructs, such as Toxic Behavior and IGD, provided preliminary evidence of external validity. Empirical evidence for the validity and internal consistency of the Tilt Scale is robust, indicating its potential utility in future research on the psychological experiences of esports players.